2015
DOI: 10.5194/hess-19-3845-2015
|View full text |Cite
|
Sign up to set email alerts
|

Use of satellite and modeled soil moisture data for predicting event soil loss at plot scale

Abstract: Abstract. The potential of coupling soil moisture and a Universal Soil Loss Equation-based (USLE-based) model for event soil loss estimation at plot scale is carefully investigated at the Masse area, in central Italy. The derived model, named Soil Moisture for Erosion (SM4E), is applied by considering the unavailability of in situ soil moisture measurements, by using the data predicted by a soil water balance model (SWBM) and derived from satellite sensors, i.e., the Advanced SCATterometer (ASCAT). The soil lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…for a very different condition from that corresponding to event runoff estimation at the plot scale. Notwithstanding this, Todisco et al (2015) concluded that the MISDc model provided fairly accurate results even at the smaller plot scale.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…for a very different condition from that corresponding to event runoff estimation at the plot scale. Notwithstanding this, Todisco et al (2015) concluded that the MISDc model provided fairly accurate results even at the smaller plot scale.…”
Section: Reviewmentioning
confidence: 99%
“…For example, an important problem in central Italy is that high soil losses can occur when the soil is initially dry but simulated runoff increases with the antecedent soil moisture conditions. Therefore, explicitly considering the soil's response to wetting in these cases (e.g., crusting phenomena) appears necessary to obtain reliable QR predictions (Todisco et al, 2015). With respect to this point, the runoff prediction method by Vandervaere et al (1998) appears to be a good candidate method deserving further investigation.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations